PENERAPAN OMOTENASHI PADA RESTORAN GOLDEN GEISHA RAMEN - Suci Sumbawati (Kepariwisataan: Jurnal Ilmiah, 2022)
Omotenashi is the Japanese culture about the way to serve customers which shown strong relationship between guest and host. Omotenashi also have similar implementation with hospitality which usually applicated at customer service activity. Omotenashi have been applied in many aspects globally. Japanese restaurant has growth significantly in recent years and hopefully many restaurants also implement Omotenashi to serve their customer. This study uses the case of Golden Geisha Ramen Restaurant in Yogyakarta to explore how the restaurant applying Omotenashi at their operational process. This paper analyzes each process from queueing process, order and payment, serving the food, and general restaurant operations. This paper offer analysis about current conditions at the restaurant and offers suggestions for restaurant for improving their implementation of Omotenashi to gain the competitive advantage of the restaurant with another competitor.